(3GdYedjI GdEOGQjI eHGOF hGUhd hYde haf (B/s - (3GdYJjHj, VQGQs; (3GdMhGQj, fVGds ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI(B, s, 2007)
(3GdYedjI GdEOGQjI,JWhQ GdacQ GdGOGQj hGdeOGQS GdGOGQjI,GdJNWjW hUfY GdbQGQGJ,GdJfXje,GdJhLjg hGdbjGOI,GdMaR hGdGJUGd,GdSdWI hGdeSDhdjI,GdJfSjb,GdQbGHIs
(3HHdjhZQGajG(B:(3U(B.267-272s
Keywords: (3GdEOGQIs; (3GdJNWjWs; (3GdJfXjes